Extracranial-to-intracranial Bypass for Pressor Dependent Cerebrovascular Insufficiency: Modified Classification and Representative Case - Heiferman, Daniel M.; Souter, John R.; Reynolds, Matthew R.; Anderson, Douglas E.; Serrone, Joseph C. (Current Neurovascular Research, 2018)
Background: While some randomized clinical trials have reduced the indications for cerebral revascularization in the secondary prevention of ischemic stroke, a distinct subset of patients with blood pressure augmentation dependent cerebrovascular insufficiency due to large vessel occlusions remains unaddressed. With the recent paradigm shifts in acute ischemic stroke care, the role of extracranial to intracranial (EC-IC) bypass must be re-addressed when endovascular intervention is not a feasible option. We submit a refined classification of cerebrovascular insufficiency with a category called Pressor-Dependent Cerebrovascular Insufficiency (PD-CVI) for whom EC-IC bypass may be indicated. Clinical Presentation: A 61-year-old female former smoker presented with one day of intermittent left faciobrachial weakness and was found to have middle cerebral artery and cervical internal carotid artery occlusions. On admission to the intensive care unit, she was found to have PD-CVI with an intravenous pressor dependent blood pressure threshold over which she had near resolution of her neurological deficits. With endovascular intervention precluded given the ICA occlusion, she underwent an urgent right sided EC-IC bypass. The procedure was without complication, with careful attention to maintaining hypertension perioperatively. She required no pressors postoperatively and was neurologically intact at three months post-operatively. Conclusion: With recent advances in acute ischemic stroke care, there remains a need for careful consideration of cerebral revascularization surgery in patients with evidence of PD-CVI who may be precluded from or failed endovascular intervention.
Keywords: carotid artery thrombosis